Pembesaran Gingiva Pada Pengguna Alat Ortodonti Cekat: Literature Review - Danti Narulita; Vera Megawati (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Orthodontic tooth movement occurs due to tissue remodeling. The success of orthodontic treatment is affected by the strength of periodontal health, oral hygiene, and orthodontics. Users of orthodontic appliances have to maintain oral hygiene to avoid periodontal disease. The purpose of this study was to evaluate and review enlargement gingiva in orthodontic user. This literature review was conducted by searching for journals, case reports and research with the keywords